Impact of different tax components, tax buoyancy and tax mix structures on economic growth and fiscal revenues in Malaysia - Samad, Muhammad Najib (2018)
This research is a study of the tax revenue (i) impact from different tax forms (that is, a given tax mix in Malaysia as at 2016) on the growth path of a country’s national income as well as (ii) how the national income growth and total fiscal revenues impact on major tax revenue forms in terms of their buoyancy. Another contribution of this study is the identification of a desirable tax mix structure of direct and indirect tax ratios that is consistent with higher economic growth. These three issues have yet been explored for almost all developing countries, as is the case for Malaysia, a middleincome developing economy. It is known from existing studies that different forms of tax have different impacts – either favourable or unfavourable – on the growth rate of Gross Domestic Product (GDP), consequently, the total revenues to government are not steady across time under different tax form mixture and under different economic conditions. A steady stream of revenue would logically enable government to plan well so it is growth-promoting for development with greater confidence if a chosen tax mix does help to attain a steady revenue stream. In order to design an appropriate tax structure that can help to steady the revenues although economic growth is likely to be buffeted by crises, this study employs an appropriate econometric procedure to explore this issue. As for the first research objective, we apply Non-Linear ARDL (Autoregressive Distributed Lag) with asymmetric effect co-integration tests with annual data over 1960-2016. The regression yields Ordinary-Leased Square (OLS) estimators to investigate the relationship between different tax forms and economic growth. Appropriate tests are done to ensure that the estimates are robust and do not suffer from autocorrelation etc. Corporate income taxes (CIT) seem to have asymmetric effect on real GDP: a 1 percent reduction in the CIT affect the GDP to reduce by 0.65 percent in the long-run, all other things held constant. However, in the short-run reduction in CIT has lagged effect on the GDP to increase by 0.069 by one year and 0.083 in lagged year two. Hence, this study extends the test of asymmetric effect to other major tax forms such as personal income tax (PIT), petroleum tax (PET), the real property gain tax (RPGT), Sales and Service tax (SST) cum Goods and Service tax (GST), Excise tax, Export and finally Import Duty. All eight different tax components are tested using models to estimate the asymmetric effect using regression technique with augmented growth control variables using total capital investments and total consumption. Findings reveal that PET significantly affect the GDP only in the short-run. Changes in PIT somehow did not have significance impact on GDP in the long-run as well as in the short-run. However, RPGT is usually considered the best tax type than can help optimize the GDP growth in the short-run. As for the buoyancy estimation of different tax forms, this study applies the ARDL cointegration approach, which could reveal long-run and short-run tax buoyancy. Instead of using bound test for cointegration, this study utilizes Error Correction Model (ECM) in order to determine long-run cointegration by using the Error Correction Term (ECT) values and testing for significance at less than 0.05. The tax revenue buoyancy is significant to GDP in the short-run with 1.24 at 0.01 significance level. This implies that total tax revenue is the short-run stabilizer that can be used as the stabilization function for planning fiscal policy. In terms of buoyancy to GDP in long run and short run, CIT shows the highest long-run tax buoyancy with 1.07 and even higher with tax reform dummy: the coefficient is 1.36. This means that growth in GDP can generate higher growth in CIT which can help the government to reduce the fiscal deficits in the long run. As for the short-run tax buoyancy, Petroleum taxes is the most buoyant with value at 4.70. The second most buoyancy is estimated for the export duty with 4.49 value; RPGT with 4.00, import duty with 2.46 and Excise tax is 1.78. All of these tax components are seen to be good tools that can help to stabilize the fiscal policy in the short-run. On the other hand, estimation of long run buoyancy to total revenue shows that Import duty is far more buoyant at 3.68. Second most buoyant to total revenues is Petroleum tax with 2.56 and thirdly is the RGPT with buoyancy value of 1.36. The buoyancy value of PIT seems to reach 0.98 without tax reforms and 0.82 with tax reforms. So, Import duty, Petroleum tax and RPGT seem to act as the total revenue stabilizer in the long-run. In the short-run, Petroleum taxes is by far the most buoyant with 3.21 to total revenue. Second buoyant item is the SST with 2.94. Both these tax forms are considered as effective short-run tools in order to help the total revenue stability. Other tax components which has buoyancy less than one are: RPGT with 0.60, Excise tax with 0.49, Export duty with 0.47, CIT with 0.31, PIT with 0.31 and Import Duty with 0.27 buoyancy. Thirdly, this study explores the desirable tax mix ratio that could promote higher economic growth. This is tested using the dynamic threshold regression, along with simulation of time series data. Direct tax and indirect taxes are two major tax revenue components that lie in the current tax mix structure. This is the first study to explore this issue by using an empirical approach to determine desirable tax mix structure ratios that are associated with GDP. The results reveal that at 95 percent confidence regions, real GDP is affected by 0.09 percent if direct tax ratio is less than 0.55. However, if direct tax ratio exceeded 55 percent share, evidence shows lower impact on real GDP at 0.07 percent initially and that could reach as low as -0.16. In summary, this study contributes to the literature in giving evidence on impacts of tax revenues components on GDP and their buoyancy to growth and also reveal on discovery on tax mix structure than can promote growth. Hence, this study can be a good reference on the evidence of taxes and growth from developing countries and for future studies. For policy, this study suggests that the government should consider to (i) reduce in share of Personal Income Tax (PIT) due to its non-significance impact on growth, (ii) to increase share in Corporate Income Tax (CIT) because CIT showed impact to the GDP and can sustain revenues in the long-run, (iii) to increase share in SST/GST and Excise Tax as this taxes showed direct impact to GDP in the short-run, (iv) to have less share in Export and Import duty due to no significance effect on GDP and finally (v) to have constant share in RGPT as this tax can be used as a tool to spur economic growth in the property market. Finally, the ideal tax mix structure that enhance positive growth is within threshold 55% (Direct to Indirect Tax ratios).